159 New epidemiological evidence on the human carcinogenic potential of acrylonitrile exposure. (11th October 2013) - Marsh, M; Downing,; Liu,; Symons,
Abstract : Objectives: Acrylonitrile (AN) is an industrial chemical used in the production of fibres, plastics, synthetic rubbers, resins and pharmaceuticals. AN has been studied extensively in exposed workers and experimental animals, yet many questions remain regarding its carcinogenic potential in humans. In 1999, the International Agency for Research on Cancer (IARC) reclassified AN as a "possible" (Group 2B) human carcinogen based largely on findings from four epidemiological studies. AN is currently under review by the US Environmental Protection Agency and is a candidate for an upcoming IARC re-evaluation. Methods: The University of Pittsburgh, Department of Biostatistics, Center for Occupational Biostatistics and Epidemiology (COBE) is engaged in a series of epidemiology studies designed to advance knowledge regarding the human carcinogenicity of AN exposure. These studies are funded by the AN Group and INEOS Nitriles, Inc. and include: An update and expansion of an earlier historical cohort study of workers exposed to AN at the Lima, OH production site owned by INEOS Nitriles. This site was one of eight AN production sites studied in the 1990s by the US National Cancer Institute (NCI) and independently studied by COBE in the same time period. A sensitivity analysis based on the INEOS Lima cohort, designed to adjust lung cancer risks in relation to AN exposure for potential confounding by smoking. While individual-level smoking data are available for most subjects, these data appear to be severely misclassified, rendering them uninformative. A sensitivity analysis similar to 2, but based on the case-cohort study of lung cancer included in the NCI cohort study. A pooled analysis of individual-level data from the two existing US historical cohort mortality studies of AN-exposed workers, the NCI cohort and the DuPont Company cohort of two AN production sites. Results: We will report current progress and available results from our series of investigations.